Academia's Golden Age : Universities in Massachusetts, 1945-1970. - Freeland, Richard M. (Oxford University Press, 1992)
This book examines the evolution of American universities during the years following World War II. Emphasizing the importance of change at the campus level, the book combines a general consideration of national trends with a close study of eight diverse universities in Massachusetts. Theeight are Harvard, M.I.T., Tufts, Brandeis, Boston University, Boston College, Northeastern and the University of Massachusetts. Broad analytic chapters examine major developments like expansion, the rise of graduate education and research, the professionalization of the faculty, and the decline ofgeneral ed.